Perlindungan Hukum bagi Konsumen yang dirugikan atas Produk Elektronik yang Tidak Bergaransi - Made Wisnuyoga Wardana; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2022)
Today more than ever before, trade activities and the high volume of trades for services or goods done by businesses are electronic products. The purpose of this research is to discuss the regulation and requirements of electronic products to be marketed and to analyze forms of legal protection for consumers for losses suffered in the use of electronic products that are not accompanied by a warranty card. The research method and problem approach used is a normative method using a conceptual approach and the rule of law. The legal sources of this research use primary, secondary and tertiary legal sources. This research uses note-taking and documentation techniques to collect the data. From the results of the research it was found that electronic products are consumer electronic products that are useful in meeting the needs of household life as a result of the production process carried out by electronic entrepreneurs, with losses for consumers in the form of repairs or returns in the form of new goods at appropriate prices and goods in accordance with similar electronic goods, and if the business actor violates the obligation, the consumer can sue according to the contents of article 19 to article 28 of the UUPK. Keywords: Business Actors, Consumers, Electronic Products